Functional Outcome of Modified Tension Band Versus-Logitudinal Anterior Band Wiring Techniques in the Management of Patella Fractures. - Muhammad Azeem Akhund, Kishore Kumar, Muhammad Faisal Shaikh,Hamid Akbar Shaikh, Muhammad Ayoub Laghari (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objectives; To compare the functional outcome of Modified tension band (MTB) versus Longitudinal anterior band (LAB) wiring techniques regarding anatomical_restoration and functional outcome of displaced transverse closed fractures of patella. Methods: A hospital based comparative cross- sectional study conducted at Department of Orthopaedic Surgery and Traumatology Liaquat University Hospital Hyderabad/Jamshoro, from January 2014 to July 2015. The totals of 30 study subjectsof fractured patella were randomly enrolled in the study. 30 patients were divided in two groups, each groups consist of 15 patients A who were stabilized with Modified tension band comprising (MTB) and group B who have longitudinal anterior band (LAB) wiring techniques. Data was documented on preassigned questionnaire and analyzed by SPSS Software. Results: Study results revealed, the mean age was 41+5.23 years. Range was 20-70 years. 22(73.33%) were male patients and 8(26.66%) were females, with male to female ratio of-2.7:1. 12 (80%) cases achieve union in MTB group out of 15, while only 7 (46.6°,0 cases in total 15 achieve union in LAB group at 6-9 weeks with statistically significant p- value 0.001. The mean healing time in MTB group was 7.3+3.1 weeks while in LAB group it was 9.1± 2.1 weeks. Functional outcome in MTB group was excellent in 53.33% patients, good was seen in 26.66% patients, fair in 13.33% patients and poor in 6.66% & in LAB group’s patients excellent was 40%, good in 26.66%, fair in 20% and poor in 26.66%. Conclusion: The modified tension band is more predictable as compare to that of Lotkelongitudinal anterior band (LAB) in management of displaced transverse closed fractures of patella regarding anatomical restoration and functional outcome.